Salpingo-Oophorectomy by transvaginal natural orifice transluminal endoscopic surgery - Jallad, Karl (2016)
BACKGROUND: Vaginal hysterectomy is the preferred route of hysterectomy in benign gynecologic disease; however, a vaginal salpingo-oophorectomy can sometimes be technically challenging. Even the most skilled vaginal surgeon will occasionally have to convert to an abdominal approach to complete the procedure. TECHNIQUE: After a vaginal hysterectomy, if the surgeon is struggling to safely complete a salpingo-oophorectomy, a natural orifice transluminal endoscopic surgery (NOTES) approach could be considered. A single port is placed in the vagina and after achieving pneumoperitoneum, an endoscope is introduced to perform a survey of the pelvis and lower abdomen. The salpingo-oophorectomy can then be completed under direct visualization by using conventional laparoscopic instruments through the vaginal port. EXPERIENCE: Salpingo-oophorectomy was successfully completed in six unembalmed cadavers and in two live patients. CONCLUSION: At the time of difficult vaginal salpingo-oophorectomy, the use of a NOTES approach could circumvent the need to convert to an abdominal route. It provides clear visualization of the entire pelvic and abdominal area and is technically feasible.